EFFORT TO INCREASE SELF-ESTEEM THROUGH POSITIVE REINFORCEMENT TECHNIQUES FOR ADOLESCENT VICTIMS OF DIVORCE - ITAK KHOIRUNNISAK; ULIN NIHAYAH; AYU FAIZA ALGHIFAHMY (Universitas Islam Negeri Mataram, 2023)
This research aims to explain the effectiveness of positive reinforcement in efforts to increase self-esteem in adolescent victims of divorce. The method used in this research is qualitative with a case study approach and descriptive analysis. This research found that: 1) Positive reinforcement is very influential in the development of self-esteem in teenagers who are victims of divorce. This research found that positive reinforcement is an effective technique in increasing and maintaining behavior; 2) A high level of self-esteem during adolescence greatly influences the process of self-acceptance and success of the adolescent in the future, and vice versa, a low level of self-esteem influences the failure of self-acceptance and the adolescent's future. 3) One of the factors that influences the development of self-esteem is relationships with other people, especially parents, family, friends and the community environment; 4) Characteristics of teenagers who have low self-esteem include: low self-esteem, no self-confidence, having a negative self-concept, even self-harm. Meanwhile, the characteristics of teenagers who have high self-esteem are feeling confident, confident in the decisions they make, having a positive self-concept, and being able to accept the negative fate of life to become a better person. Research recommends that parents, teachers, and stakeholders provide emotional support, maintain open communication, and seek professional help if necessary to help teens overcome the negative impact of divorce on their self-esteem. The research concluded that positive reinforcement is an effective technique in increasing self-esteem in adolescent victims of divorce.